2019
DOI: 10.5171/2019.253359
|View full text |Cite
|
Sign up to set email alerts
|

Book Piracy Behavior among College Students in Indonesia

Abstract: Piracy, or the counterfeiting of a product, remains an important global issue. This research aims to examine the factors that influence university students' intention in the piracy of academic books. The research conducted is based on previous attitudes toward piracy behavior, subjective norms, and perceived behavioral control. Piracy is both unethical and illegal, and this study develops the theory of planned behavior (TPB) by adding ethics theory addressing moral obligation and perceived benefits and deterre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Meanwhile, moral obligation has no effect on the intention of accounting students to cheat on online exams. This result is not in accordance with the research of Alleyne & Phillips, (2011);Fitriasih et al, (2019), but it is consistent with the research of Sayal & Singh, (2020). Although it has no effect on intention, moral obligation has a significant and negative effect on subjective norm.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Meanwhile, moral obligation has no effect on the intention of accounting students to cheat on online exams. This result is not in accordance with the research of Alleyne & Phillips, (2011);Fitriasih et al, (2019), but it is consistent with the research of Sayal & Singh, (2020). Although it has no effect on intention, moral obligation has a significant and negative effect on subjective norm.…”
Section: Discussionsupporting
confidence: 46%
“…SEM is chosen because it offers a simultaneous testing for all hypotheses in this complex model and could capture unobserved variables (Gudono, 2014). Besides, there are several research related to fraud who also utilized SEM for their data analysis such as Carmen et al, (2014); Casidy et al, (2016); Fitriasih et al, (2019); Hati et al, (2019). There are 2 tests in SEM, namely the Structural Model & Measurement Model (Hair et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study explained that publishers' choice not to print e-books or make them available in minimal quantities further boosts book piracy statistics in these channels (Gudinavičius & Grigas, 2022). In Indonesia, Fitirasih et al ( 2019) also revealed that students are motivated to use pirated books because of the benefits they receive, and they have no fear of sanctions for using them (Fitriasih et al, 2019). Those who choose to buy books legally are also not motivated by copyright infringement sanctions but by their moral and ethical beliefs (Hati et al, 2020).…”
Section: Online Sale Of Pirated Books From a Legal And Moral Perspectivementioning
confidence: 99%